Re-thinking of Agenda Setting Theory : Study Case of the 2014 Presidential Election in Indonesia, and as Impact of a New Media Exposure - Solikhah Yuliatiningtyas (Metafora: Education, Social Sciences and Humanities Journal, 2023)
Agenda setting theory was experiencing the evolution since second level agenda took place in 1972 in regards to explain the understanding of political behavior during the election campaigning worldwide. Although finally it accepted to use 3 layers in agenda setting theory effects, but in the process of political communication there is always unexpected result studies shown. This study case examines the second level agenda setting theory influenced by both traditional and new/digital media exposure during the 2014 presidential election campaigning in Indonesia. It shows evidence there are some factors influenced the winning of Jokowi in the 2014 presidential election outside mass media exposure, especially the role of new media campaigning (e-political marketing). Also, compare to similar previous studies in some different countries to enrich the evidence, to criticize the existing theory of agenda setting effect which is has been accepted widely. Finally, the findings recommend to ‘re-thinking’ about the second level of agenda setting theory to explain a way of demonstrating the effects of news content among traditional mass media by provide evidence the attributes to shape opinions and then change the political behavior during the campaigning period among society. While second level agenda setting is relatively still new, evolving in 1997, it has enrich as well as strengthen the result studies in which offers support the understanding of mass media effect into political behavior.